Pengaruh Digital Marketing Dan E-Crm Terhadap Customer Loyalty - Axliano, Anak Agung Gaizka; Ikhram, M. Abdi Dzil (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2024)
The efforts of PT Bank Sinarmas Syariah to use internet technology and social media need to be supported with easy and efficient marketing and services. The bank has also developed an application called SimobiPlus, which is used to provide 24-hour service and enables marketing easily reachable by the customers. The objective of this research is to identify the effects of digital marketing and E-CRM on customer loyalty using quantitative descriptive method. A descriptive research seeks for the value certainty from independent variables with neither making comparison nor drawing relationship with other variables. Using purposive sampling technique, 195 people who meet the predetermined criteria were selected as the sample. The results of the analysis using multiple linear regression indicate that digital marketing (X1) and E-CRM (X2) have positive and significant impacts on customer loyalty (Y).   Abstrak The efforts of PT Bank Sinarmas Syariah to use internet technology and social media need to be supported with easy and efficient marketing and services. The bank has also developed an application called SimobiPlus, which is used to provide 24-hour service and enables marketing easily reachable by the customers. The objective of this research is to identify the effects of digital marketing and E-CRM on customer loyalty using quantitative descriptive method. Descriptive research seeks for the value certainty from independent variables with neither making comparison nor drawing relationship with other variables. Using purposive sampling technique, 195 people who meet the predetermined criteria were selected as the sample. The results of the analysis using multiple linear regression indicate that digital marketing (X1) and E-CRM (X2) have positive and significant impacts on customer loyalty (Y).